The critical effect of rail vertical phase response in railway curve squeal generation. (1st February 2020) - Lai, Van-Vuong; Chiello, Olivier; Brunel, Jean-François; Dufrénoy, Philippe
Highlights: Even with a constant Coulomb friction, instabilities can occur because of the coupling between normal and tangential dynamics in wheel/rail systems. Two instability mechanisms: Classical mode coupling and instabilities in a single wheel mode when the track dynamical behavior is included. The combination of friction and the equivalent damper behavior of the infinite track added to a single wheel mode may destabilize the system, leading to self-sustained vibration and squeal noise. Graphical abstract: Abstract: Squeal of rail-bound vehicles emitted in tight curves is characterized by high sound pressure levels at pure medium and high frequencies. Many models have been proposed in the literature to explain the occurrence of this noise with different instability mechanisms: negative damping due to falling friction or instability with a constant friction coefficient. The aim of the paper is to contribute to the understanding of the instability mechanisms in the case of a constant friction coefficient. A stability analysis of the wheel/rail contact dynamics in curve is performed by using an equivalent point contact model combined with wheel and rail modal bases. Results show that even with an assumption of a constant Coulomb friction coefficient, two types of instabilities may occur in the wheel/rail system: classical mode coupling and instabilities due to negative damping added to a single wheel mode when the track dynamical behavior, especially in the vertical direction, is included. For this second type of instabilities, an 1-degree of freedom model can be formulated. By using this model, it is found that the equivalent damper behavior of the infinite track is the origin of these instabilities.